CIO and ring graphs: Deficiency and testing. (March 2017) - Gitler, Isidoro; Reyes, Enrique; Vega, Juan A.
Abstract: We give a polynomial time algorithm that tests whether a graph is a theta-ring graph or equivalently if a graph has the ∀ θ ∃ Δ -property (each chorded-theta has a transversal triangle). It is known that G is a theta-ring graph if and only if G is a CI O graph (each toric ideal associated to an edge orientation of G is a binomial complete intersection). In particular ring graphs are theta-ring graphs. We prove that the forbidden induced subgraphs that characterize ring graphs are chorded-thetas and K 4 . We introduce a new graph invariant, the CI O deficiency. This invariant has the property that graphs with CI O deficiency zero are exactly CI O graphs.